SAT0021 Prognostic Value of Salivary Gland Ultrasonography (SGUS) in Primary SjÖGren's Syndrome. (10th June 2014) - Baldini, C.; Luciano, N.; Sernissi, F.; Martini, D.; Francesco, F.; Gaia, T.; Mosca, M.; Bombardieri, S.
Abstract : Objectives: Recently, salivary gland ultrasonography (SGUS) has been presented as a promising diagnostic tool for primary Sjögren's syndrome (pSS). The aim of the current study was to assess the prognostic value of SGUS in the assessment and risk stratification of pSS patients into high or low risk subgroups with regard to lymphoma development and systemic complications. Methods: Unselected patients with a diagnosis of pSS made according to the AECG 2002 criteria were consecutively enrolled in this study. Patients' clinical and serological features were prospectively collected particularly focusing on variables generally associated to pSS severity. The ESSDAI score was calculated to quantify pSS disease activity. SGUS was carried out by the same radiologist and the following US parameters were recorded: size, parenchymal echogenicity and inhomogeneity in the parotid and submandibular glands on both sides. A modified version of a previously reported ultrasound scoring system (De Vita et al 1992, cut-off>2) was used to grade the echostructure alterations of the salivary glands. Comparison in terms of continuous data were determined using independent sample t tests or Mann–Whitney tests, and in terms of proportions using contingency table analysis and chi square test. Spearman's rank correlation coefficients were calculated between SGUS scores and disease duration, age at the diagnosis, ESSDAI score, IgG levels, C3 and C4 levels, white blood cells, minor salivary gland focus score (MSG FS) and salivary flow rate. Results: One hundred and sixty female patients with pSS were enrolled in this study (median age=57.5 years (IQR 46.25-68); median follow-up=3 years (IQR 1-8). A pathological SGUS score ≥2 was found in 66/160 (41%) patients. Abnormal SGUS scores were significantly more frequent in patients with a systemic disease with respect to those with a pure "exocrinopathy", and in those with a positivity for anti-Ro/SSA antibodies. A positive correlation was observed between the SGUS score and ESSDAI (r=0.525; p<0.0001), ESR (r=0.223; p=0.02) and higher levels of IgG (r=0.249; p=0.02). A negative correlation was found between the SGUS score and the age of the patients (r=-0.205; p=0.003), C4 levels (r=-0.221; p=0.02), white blood cells count (r=-0.207; p=0.02) and salivary flow rate (r=-0.295; p<0.0001). Conclusions: Our findings outline the usefulness of SGUS for the identification of patients with high disease activity and support its routinary use in pSS assessment. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4468